Analisis Idiom Bahasa Jepang yang Terbentuk dari Kata “Neko” (Fokus pada Bagian Tubuh) - Ariestafuri, Nurza (Universitas Negeri Jakarta, 2017)
In this paper, the author analyzes the meaning of Japanese idiom (kanyouku) which is formed from the word 'neko' but only focused on body parts. This research is motivated by the previous findings which states that Japanese has many idioms containing the word 'neko '(cat) at most compared to the language of any country. The purpose of this study is to determine the formation and meaning of idiom in order to avoid errors of use by Japanese language learners. The method used to analyze the idiom is descriptive qualitative by describing lexical and idiomatic meanings. The conclusion of this research is the Japanese idiom that uses the cat body part mostly present in the form of a metaphor that adapts the similarity of the animal's characteristic itself.